2009
DOI: 10.1090/s0894-0347-09-00650-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of the convergence of the empirical covariance matrix in log-concave ensembles

Abstract: Let K be an isotropic convex body in R n . Given ε > 0, how many independent points X i uniformly distributed on K are needed for the empirical covariance matrix to approximate the identity up to ε with overwhelming probability? Our paper answers this question from [12]. More precisely, let X ∈ R n be a centered random vector with a log-concave distribution and with the identity as covariance matrix. An example of such a vector X is a random point in an isotropic convex body. We show that for any ε > 0, there … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
283
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 164 publications
(292 citation statements)
references
References 25 publications
(35 reference statements)
5
283
0
4
Order By: Relevance
“…When combined with estimates for the operator norm of the matrix Γ, obtained recently in [2], the above theorem also yields a corollary about the tail behavior of the so called condition number of the matrix Γ (denoted by (Γ)). The question about its behavior for random matrices was raised by Smale [22] in connection with stability of numerical algorithms for solving large systems of linear equations.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…When combined with estimates for the operator norm of the matrix Γ, obtained recently in [2], the above theorem also yields a corollary about the tail behavior of the so called condition number of the matrix Γ (denoted by (Γ)). The question about its behavior for random matrices was raised by Smale [22] in connection with stability of numerical algorithms for solving large systems of linear equations.…”
mentioning
confidence: 81%
“…On the other hand, Proposition 2.10 with = 10 and = 10 /(2 6 ) gives for any ∈ (0, 1), Let us now turn to the proof of (2). Let be the constant in (1).…”
Section: ℙ( Infmentioning
confidence: 97%
See 1 more Smart Citation
“…The articles [1], [2] and [3] considered random matrices with independent columns, and investigated high dimensional geometric properties of the convex hull of the columns and the RIP for various models of matrices, including the log-concave Ensemble build with independent isotropic log-concave columns. It was shown that various properties of random vectors can be efficiently studied via operator norms and the parameter Γ n,m recalled below.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that various properties of random vectors can be efficiently studied via operator norms and the parameter Γ n,m recalled below. In order to control this parameter an efficient technique of chaining was developed in [1] and [2].…”
Section: Introductionmentioning
confidence: 99%